2017
DOI: 10.1007/s12223-016-0490-7
|View full text |Cite
|
Sign up to set email alerts
|

Raoultella spp.—clinical significance, infections and susceptibility to antibiotics

Abstract: The genus Raoultella belongs to the family of Enterobacteriaceae. Raoultella spp. are Gram-negative, aerobic, non-motile rods. This genus can be distinguished from the genus Klebsiella, in that genus use histamine as the only source of carbon in the medium. Also, Raoultella grow at 4 °C and do not produce gas from lactose at 44.5 °C. Raoultella sp. is known to inhabit natural environments (water, soil, plants). The reservoir of Raoultella is the gastrointestinal tract and upper respiratory tract. Raoultella sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
67
0
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 87 publications
(83 citation statements)
references
References 91 publications
1
67
0
5
Order By: Relevance
“…R. planticola (Drancourt et al 2001) is a bacterium that is found in soil and on plants, occasionally also on humans and animals. It can assimilate starch (Hii et al 2012), has been found in farms running dairy production and is an opportunistic pathogen (Sekowska 2017; Zadoks et al 2011). P. agglomerans lives in a variety of habitats, including plants, arthropods or vertebrates.…”
Section: Resultsmentioning
confidence: 99%
“…R. planticola (Drancourt et al 2001) is a bacterium that is found in soil and on plants, occasionally also on humans and animals. It can assimilate starch (Hii et al 2012), has been found in farms running dairy production and is an opportunistic pathogen (Sekowska 2017; Zadoks et al 2011). P. agglomerans lives in a variety of habitats, including plants, arthropods or vertebrates.…”
Section: Resultsmentioning
confidence: 99%
“…are gram-negative aerobic rods belonging to the Enterobacteriaceae family. They typically inhabit natural environments but were also recognized as opportunistic human pathogens (Sękowska 2017). These bacteria are naturally resistant to aminopenicillins because of the possession of chromosomal, class A β-lactamase genes (Walckenaer et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…33 Most species in the genus Raoultella are usually broadly sensitive to antibiotics based on the isolates from case series in the literature. 34 Similarly to some Klebsiella species, Raoultella spp. exhibit intrinsic resistance to ampicillin and ticarcillin which are the result of chromosomally encoded beta-lactamases.…”
Section: Virulence and Resistancementioning
confidence: 99%
“…exhibit intrinsic resistance to ampicillin and ticarcillin which are the result of chromosomally encoded beta-lactamases. [34][35][36][37] Chun et al (2015) reported a series of 16 patients with isolates showing antibiotic susceptibility to cephalosporins ranging from 69% to 100%, 93% susceptibility to amoxicillin/clavulanic acid, 88% to trimethoprim/sulfamethoxazole (TMP-SMX) and 100% to meropenem, imipenem and piperacillin/ tazobactam. 4 reported, in the largest series published, that resistance to amoxicillin/clavulanic acid, ceftriaxone, quinolones, TMP-SMX and aminoglycosides were 16%, 4%, 6%, 10 and 1% respectively.…”
Section: Virulence and Resistancementioning
confidence: 99%
See 1 more Smart Citation